Otolith And Growth Pattern Layang Fish, Decapterus Muroadsi Temminck & Schlegel, 1844 In Manado Bay - Yulianti Umar; Fransine B. Manginsela; Ruddy D. Moningkey (Jurnal Ilmiah PLATAX, 2019)
The aim of this research is to know the distribution of the size of Decapterus muroadsi, to describe otolit that is otolith length (Po), width otolith (Lo), perimeter / otolith circumference (Ko), otolith area (Ao), and determine the relationship of total length and body weight of fish kite Decapterus muroadsi in Manado Bay. The sampling was conducted in August - December 2017 of the gliders obtained during the study of 135 individuals in which males were 87 individuals and 48 female individuals. Distribution of the total length of the globe and the body height of the globe fish 190 mm - 225 mm, weighs 63 grams - 154 grams, the female fish has a total length of 205 mm - 250 mm, and weighst 88 grams - 159 grams. To know the morphometric perimeter otolith left and right perimeter otolith fish taken to be taken as otolith samples of male fish (15 individuals) and females (15 individuals). The results of the comparison analysis were found for the left and right otolith of male trooper with otolith length (Po) 0.796, perimeterr / otolith circumference (Ko) 0.621, and otolith area (Ao) 0.268 and females with 0.027 otolith (Po) 0.057, perimeter / otolith (Ko) 0.231, and otolith area (Ao) 0.858, males and females did not differ significantly between left otolith and right otolite where t-hit <from t-table as for otolith (O2) 2,371 and otolith otolith otolith (Lo) 2,952 differs markedly where t-hit> from t-table. Kites, Decapterus muroadsi used as a sample in the study were 135 individuals divided into 3 parts, namely males and females and combined (males and females). Based on the result of growth pattern analysis on the value of the fish b of the Decapterus muroadsi male has t-hit> t-table (4E - 06> 1,998) and mixed (and female) have t-hit> t-table (4E-06 - 1,997) Therefore H1 is accepted as (allometric) and females have t-hit <t-table (3E-O6-1,679) has a value b where hypothesis H1 is accepted as isometric. Keywords: Decapterus muroadsi, Describing, Otolith, male, females ABSTRAKPenelitian ini bertujuan untuk mengetahui sebaran ukuran ikan layang Decapterus muroadsi, mendeskripsikan otolit yakni panjang otolit (Po), lebar otolit (Lo), perimeter/keliling otolit (Ko), area otolit (Ao), dan menentukan hubungan panjang total dan berat tubuh ikan layang Decapterus muroadsi di Teluk Manado. Pengambilan sampel  ini dilakukan pada bulan Agustus – Desember 2017 ikan layang yang di peroleh selama penelitian sebanyak 135 individu di mana jantan 87 individu dan betina 48 individu. Sebaran ukuran panjang total ikan layang dan berat tubuh ikan layang jantan 190 mm – 225 mm, berat 63 gram – 154 gram, ikan layang betina memiliki panjang total 205 mm – 250 mm, dan berat 88 gram – 159 gram, Untuk mengetahui perimeter morfometrik otolit kiri dan kanan perimeter otolit ikan layang yang diambil untuk dijadikan sampel otolit ikan layang jantan berjumlah (15 individu) dan betina (15 individu). Hasil analisis perbandingan ternyata untuk otolit kiri dan kanan ikan layang jantan dengan Panjang otolit (Po) 0,796, perimeterr / keliling otolit (Ko) 0,621, dan  area otolit (Ao) 0,268 dan betina dengan Panjang otolit (Po) 0,057, perimeter/keliling otolit (Ko) 0,231, dan area otolit (Ao) 0,858, jantan dan betina tidak berbeda nyata antara otolit kiri dan otolit kanan di mana t-hit < dari t-tabel adapun untuk otolit jantan lebar otolit (Lo) 2,371 dan otolit betina  lebar otolit (Lo) 2,952 berbeda nyata di mana t-hit > dari t-tabel. Ikan layang, Decapterus muroadsi yang digunakan sebagai sampel dalam penelitian berjumlah 135 individu yang di bagi dalam 3 bagian yaitu jantan dan betina serta gabungan (jantan dan betina). Berdasarkan hasil analisis pola pertumbuhan terhadap nilai b ikan layang Decapterus muroadsi jantan memiliki t-hit> t-tabel (4E – 06 >1,998) serta campuran (jantan dan betina) memiliki t-hit> t-tabel (4E-06 – 1,997) Maka dari itu H1 di terima sebagai (allometrik) dan betina memiliki t-hit< t-tabel (3E-O6– 1,679) memiliki nilai b dimana hipotesis H1 diterima sebagai isometrik.Kata kunci : Decapterus muroadsi, mendeskripsikan, otolit, jantan, betina